Determinan Penghimpunan Dana Pihak Ketiga Bank Syariah di Indonesia Tahun 2017.1. – 2021.12. - Junjun Arip Nugraha (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2022)
This research is an explanatory study to explain the determinants of third party fund raising of Islamic banks as the dependent variable in Indonesia using the Econometrics Partial Adjustment Model (PAM) approach. The independent variable of the research is derived from the construct of the marketing environment which is divided into external factors and internal factors. The two factors are further broken down into seven variables. It is concluded that the PAM model has been successful in estimating the model and has passed the classical assumption test. During the research period, namely in 2017.1. – 2021.12, all variables have a strong relationship and have a simultaneous effect on the dependent variable. Only promotion costs and the number of office networks partially have a significant effect on the dependent variable. The number of office networks is the most significant variable.